PO54 | FATTY INFILTRATION AND POTENTIAL ADIPOGENIC SHIFT OF SKELETAL MUSCLE CELLS: MULTIPARAMETRIC HISTOLOGICAL ANALYSIS OF MYOSTEATOSIS (European Journal of Histochemistry)
Myosteatosis, defined as an ectopic fat accumulation within skeletal muscle, has gained increasing clinical relevance as it fits within the context of metabolic disorders and aging. Elderly, sedentary, obese, type 2 diabetic and dyslipidemic patients are more prone, and it worsens the prognosis in both malignant and non-malignant diseases1. Currently, no effective therapeutic interventions exist; prevention through lifestyle modifications remains the only option. The prevailing theory suggests that ectopic fat originates from interstitial fibro-adipogenic precursors (FAPs), which tend to follow an adipogenic fate under chronic proinflammatory stimuli2. Since histological analysis is the gold standard for assessing myosteatosis - allowing the evaluation of both morphological changes in muscle cells and lipid accumulation, - we performed a multiparametric histological investigation to highlight pathological alterations in skeletal muscle and to explore the potential adipogenic shift (transdifferentiation) of muscle fibers due to lipid accumulation. Biopsy samples from the Vastus lateralismuscle were collected from patients undergoing arthroplasty surgery (M:F = 1:2; mean age ± SD = 71.9±7.1) and processed according to FFPE (“Formalin-fixed Paraffin Embedding”), cryo-embedding and resin embedding protocols. FFPE sections were stained with hematoxylin-eosin, Masson’s trichrome and indirect immunohistochemistry for perilipin-1 and a-sarcomeric actin. Cryosections were stained with lipophilic dyes Sudan Black B and Oil Red-O. Our analysis confirms pathological changes of muscle cells3 like atrophy, necrosis, fragmentation, vacuolization and significant intramyocellular lipids and intramuscolar fat deposition. Most importantly, our study suggests that massive fat accumulation in skeletal muscle is not solely due to ectopic infiltration but also related to a subpopolation of muscle cells that may lose its contractile phenotype, acquiring adipocyte-like morphological features.